Non suitability of silver ion conducting polymer electrolytes based on chitosan mediated by barium titanate (BaTiO3) for electrochemical device applications - Aziz, Shujahadeen B.; Abdullah, Ranjdar M.; Kadir, Mohd Fakhrul Zamani; Ahmed, Hameed M. (Elsevier, 2019)
In this study, we report the non-suitability of silver ion conducting polymer electrolytes mediated by barium titanate (BaTiO3) for electrochemical device applications. Various amounts of BaTiO3 fillers have been added to chitosan: silver triflate (CS:AgTf) solution to prepare polymer composites. Electrical impedance spectroscopy (EIS) has been used to characterize electrical properties of the samples. Charge transfer resistance has been correctly estimated for the samples using electrical equivalent circuit (EEC) model. At 3 and 5 wt % of BaTiO3 filler, the charge transfer resistance was found to increase and diameter of the impedance plots are shown to be widened due to the increase of grain boundaries. The dielectric constant is also observed to decrease with the increase of BaTiO3 concentration. DC conductivities for the composite samples are estimated from AC conductivity spectra. The DC conductivity was found to decrease from 4.7 × 10−7 S/cm to 5.4 × 10−9 S/cm for CS:AgTf system incorporated with BaTiO3 filler. Such decrease has revealed that the electrolytes are not suitable for electrochemical device applications. Shifting of relaxation peaks of imaginary part of electric modulus towards low frequency side has indicated the increase of relaxation time and hence the decrease in DC conductivity. The relaxation processes are also studied using Argand plots. The existence of metallic silver nanoparticles has been examined via ultraviolet–visible (UV–Vis) spectroscopy. The UV–Vis spectra showed that surface plasmon resonance (SPR) peaks are broadened and increased in their intensity as the BaTiO3 concentration increased from 1 to 3 wt %. This implied that the reduction rate of silver ions to silver nanoparticles is increased. Moreover, disappearance of SPR peak was found for the BaTiO3 concentration of 5 wt %, revealing the bulk formation of silver metals. Transmission electron microscopy (TEM) images were obtained for the samples, in which the formation of bulk metallic sizes of silvers was found to be obvious. This growth of bulk silver metals at high BaTiO3 concentration was further supported by optical and scanning electron microscopy (SEM) techniques. The distribution of white specs due to silver nanoparticles on the surface of chitosan-silver triflate solid film was investigated. Large white sheets were appeared on the surface of CS:AgTf incorporated with 5 wt% BaTiO3 and related to the huge amount of aggregated metallic silver particles. Sharp intense peaks due to metallic silver particles and weak peaks due to BaTiO3 fillers have been observed in the analyses of energy dispersive X-ray (EDX) spectra.